No smoking within nine metres of discipline limits (Medicine Anthropology Theory, 2014)
I seek to open the social practice of smoking to anthropological enquiry that has been largely caught up in the agenda of cessation – to the point that it is difficult to examine it outside this frame without being accused of advancing the interests of Big Tobacco. Analysis has also been foreclosed by adherence to frames that privilege rationality. Smoking behaviour becomes understandable and translatable via explanations of addiction or ignorance: it is rational for the addict to source her drug, and rational for the smoker ignorant of its harms to continue smoking. Equally, using a rational frame anthropologists might explain smoking practice in relation to pleasure – if they are not wedded to a cessation agenda – as maximising pleasure might also be rational, as might any practice if only one can understand the agent’s motivations. I argue for an anthropological analysis of smoking that permits more than translation.